Praktik Ethical Hacking Untuk Menjamin Keamanan Sistem Sebagai Upaya Mewujudkan Keamanan dan Kerahasiaan Data Pribadi: Studi Komparasi Pengaturan Indonesia dan Kanada - Prabhaswari, Amaraduhita Laksmi; Marlyna, Henny; Anggraini, Ayu Galuh (UI Scholars Hub, 2025)
In the digital era that is increasingly integrated with electronic systems and technology, issues related to the security and confidentiality of personal data have become a crucial issue, especially in the midst of the increasing number of cyber attacks. The urgency of this protection is increasingly urgent along with the complex use of technology by PSE, both public and private. The practice of ethical hacking by contract based or policy-based emerged as a proactive effort in identifying and addressing security gaps in a system. Although in Canada this practice has been recognized as part of national security policy (RVDP), Indonesia has not yet regulated and opened the policy (/VVIP) to the public. This research aims to analyze ethical hacking arrangements in Indonesia and Canada including protection policies for ethical hackers, both certified and voluntary. The method used is doctrinal research with the approach of existing legislation and policies, and supported by interview data from credible sources. The results show that although Canada and Indonesia both have such policies, Canada's policy is nationally applicable and open as a form of collaboration between the government, PSEs, and ethical hackers, and provides more guaranteed protection for them. Meanwhile, in Indonesia, the policy is still an internal regulation of an institution that is not applicable and binding for the wider community.